Catolicismo e educação na Carta Pastoral de Dom Sebastião Leme (1916) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The aim of this dissertation is to analyze the Pastoral Letter, gretting the diocesans (1916) written by dom Sebastião Leme (1882-1942), Metropolitan Archbishop of Olinda. It highlights his propositions and their impact on the educational field, in the context of the relations between Church and State during the First Republic. Our investigation is situated within the scope of the Education History and seeks to broaden its possibilities of analysis through dialog with Intellectual History and Sociology. The conceptual tools used in the research include the categories developed by Pierre Bourdieu. Dom Leme's Pastoral Letter, published in 1916, on the occasion of his inauguration to the Archdiocese of Olinda (from 1918, Archdiocese of Olinda and Recife), is the historical source selected for our research. A facsimile copy of the first edition of the document was obtained from the virtual repository of the Catholic University of America, Washinghton-DC. This edition was published by Typologia Vozes de Petrópolis - it has 138 pages and is divided into 4 parts. Sebastião Leme was one of the most important Catholic intellectual leaders of the first half of the 20th century, notable for his efforts to restore the relevance of Catholic doctrine and values in the public debate. In this sense, he promoted the strategy of mobilizing the laity so that they would occupy positions in different social fields, working on behalf of the Church's interests, at the frontier of the political, religious and educational fields. This investigation analyzes the structure, content and historical meaning of Dom Leme's Pastoral Letter, highlighting it as a key document - considering its significant impact in the context of the First Republic - for understanding the ideas and strategies proposed by the archbishop with a view to the Catholic restoration of the country. As results of our research, some key elements stand out throughout Dom Leme's speech in his Pastoral Letter, namely: the relevance he gave to what he understood to be the problem of religious ignorance in Brazil, interpreted as a real impediment to the cohesion and social mobilization of the Catholics; the laicization of the Brazilian State, jointly with the secularization of national culture, in a typical phenomenon of modernity promoted by the Republic, which, in Dom Leme's assessment, implied the loss of the people's historic Catholic identity; and also the staunch defense of the Catholic presence in the educational field, notably through religious education as a subject in state schools, to which was added the demand for state subsidy of Catholic schools. Sebastião Leme worked in favor of a conception of faith supported by knowledge and rationality, as a way to overcome a religiosity guided by affective aspects, which, according to him, opened the door to religious ignorance. The repercussions of the Pastoral Letter provided dom Leme visibility and prestige, both Catholic and secular circles, which solidified his intellectual leadership and leveraged the project of a neo- Christianity in Brazil.
Keywords: Dom Sebastião Leme; Carta Pastoral; Intelectuais católicos; Campo educacional; Dom Sebastião Leme; Pastoral Letter; Catholic intellectuals; Educational field; CNPQ::CIENCIAS HUMANAS::EDUCACAO